An Exquisite Politeness: The Royal Commission on Genetic Modification and the Redefining of the Treaty of Waitangi - Jackson, Moana (2001)
Keywords: marginalisation; tiriti o waitangi/treaty of waitangi

Submission on Water Issues in Aotearoa New Zealand - Bargh, Dr Maria (Office of the High Commissioner for Human Rights, 2007)
Keywords: government; hapū; iwi; tino rangatiratanga; tiriti o waitangi/treaty of waitangi; water rights

He wharemoa te rakau, ka mahue. Māori engagement with local government: knowledge, experiences, and recommendations. - Cheyne, Christine M; Tawhai, Veronica M H (2007)

The future of rongoa Maori: wellbeing and sustainability. - Ahuriri-Driscoll, A.; Baker, V.; Hepi, M.; Hudson, M.; Mika, C.; Tiakiwai, S. (2008)
Rongoa Maori is a holistic system of healing that has developed out of Maori cultural traditions. It has a long history of usage and credibility among Maori, and increased interest in its revival and sustainability has prompted calls for its formalisation within the New Zealand public health system. Objective and methods The objectives of the research project were to: - Examine the contribution of rongoa Maori to indigenous wellbeing, and - Identify issues for the ongoing sustainability of traditional Maori healing in New Zealand. The research process was lead by Maori researchers in collaboration with Maori healers and stakeholders. Two literature reviews were undertaken; one to provide understanding of international developments in traditional medicine, and a second to review national policy/literature related to rongoa Maori. Four focus groups and five workshops were held with groups in five communities to explore current rongoa practice and service delivery and drivers/barriers to its ongoing utilisation. The participant groups were healers and their associates, and health and local authority stakeholders.
Keywords: hauora; health; rongoa